Dreams of a music enthusiast: analysis of a long dream series - Markert, Bettina; Schredl, Michael (International journal of dream research, 2024)
In this study, we analyzed a voice-recorded dream series (N=625) from a music enthusiast with severe sight impairment. We found a very high frequency of musical dreams (58.2%). Our findings supported the continuity hypothesis, suggesting that music engagement impacts dream content. General music themes and listening to music were more predominant, than dreams with making music, singing, and creativity. The finding that the frequency of musical dreams is even higher than in professional musicians, might be explained by the dreamer's musical enthusiasm combined with her severe sight impairment, resulting in her reliance on auditory experiences. In addition, music celebrities (e.g., Celine Dion) occurred relatively often. Notably, making and/or listening to music in dreams often conveyed negative emotions, while singing was associated with mostly positive emotions. These negative emotions are related to problems with musical performance and scary feelings while listening to specific music.